1992
DOI: 10.1108/eb028255
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the External Audit Fee of UK Unquoted Companies — Some New Evidence

Abstract: In recent years there has been a growing debate, in the academic, professional and popular literature, on the audit ‘expectation gap’ and the role and independence of the auditor. As noted by Waller (1991): ‘Much of the criticism of auditors concerns an apparent lack of impartiality. Outsiders feel that independence is compromised… who knows what short cuts are taken by auditors keen to keep “well in” with management for the sake of winning profitable consultancy work to supplement the audit fee?’

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Hence, the study hypothesis regarding the association between auditee complexity and audit fees is proven and the variation of audit fees for the machinery equipment companies is significantly affected by auditee complexity. The findings were therefore consistent with the results of studies conducted by Brinn et al (1992) in the UK, Hay et al (2006) in New Zealand, Naser and Nuseibeh (2008) in Jordon, and Thinggaard and Kiertzner (2008) in Denmark, who found that auditee complexity has a significant impact on determining audit fees. However, these results were inconsistent with the findings of Zhang and Myrteza (1996), and Ahmed and Goyal (2005), who found a negative correlation between auditee complexity and audit fees.…”
Section: Discussion Of the Study's Resultssupporting
confidence: 89%
“…Hence, the study hypothesis regarding the association between auditee complexity and audit fees is proven and the variation of audit fees for the machinery equipment companies is significantly affected by auditee complexity. The findings were therefore consistent with the results of studies conducted by Brinn et al (1992) in the UK, Hay et al (2006) in New Zealand, Naser and Nuseibeh (2008) in Jordon, and Thinggaard and Kiertzner (2008) in Denmark, who found that auditee complexity has a significant impact on determining audit fees. However, these results were inconsistent with the findings of Zhang and Myrteza (1996), and Ahmed and Goyal (2005), who found a negative correlation between auditee complexity and audit fees.…”
Section: Discussion Of the Study's Resultssupporting
confidence: 89%
“…With reference to the extensive previous hypotheses development and empirical evidence contained in the extant literature (see e.g. Brinn et al, 1991;Yardley et al, 1992, for reviews), a positive relationship is expected between audit fees and the firm size and complexity variables (SIZE, SUBS, FORS). These variables proxy for audit scale/effort and audit complexity and represent sales, number of subsidiaries and the ratio of foreign to total subsidiaries respectively.…”
Section: Control Variablesmentioning
confidence: 99%
“…Norway: Firth, 1997. UK: Taylor and Baker, 1981; Taffler and Ramalinggam, 1982; Haskin and Williams, 1988; Brinn et al , 1991; Chan et al , 1993; Brinn et al , 1994; Pong and Whittington, 1994; O'Sullivan and Diacon, 1994; Che Ahmed and Houghton, 1996; Gregory and Collier, 1996; Ezzamel et al , 1996; Iyer and Iyer, 1996; O'Sullivan, 2000; Peel and Clatworthy, 2001; Chung and Narasimhan, 2002; Ezzamel et al , 2002; Niemi, 2002; O'Sullivan and Diacon, 2002; Simon and Taylor, 2002).…”
Section: Introductionmentioning
confidence: 99%